Constructing and Solving the System of Linear Equations Produced From LFSR Generators - Ali, F.H.; Hussein, A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Linear Feedback Shift Register (LFSR) systems are used  widely in stream cipher systems field. Any system of LFSR's which wauldn't be attacked must first construct the system of linear equations of the LFSR unit. In this paper methods are developed to construct a system of linear/nonlinear equations of key generator (a LFSR's system) where the effect of combining (Boolean) function of LFSR is obvious. Before solving the system of linear/nonlinear equations by using one of the known classical methods, we have to test the uniqueness of the solution. Finding the solution to these systems mean finding the initial values of the LFSR's of the generator. Two known generators are used to test and apply the ideas of the paper, these generators are the linear system and Bruer system.